Influence of needle size and injection angle on the distribution pattern of facial soft tissue fillers. (8th July 2019) - Pavicic, Tatjana; Mohmand, Humayun M.; Yankova, Mariya; Schenck, Thilo L.; Frank, Konstantin; Freytag, David L.; Green, Jeremy B.; Hamade, Hassan; Cassuto, Daniel; Cotofana, Sebastian
Abstract: Background: Soft tissue filler injections are performed using either sharp‐tip needles or blunt‐tip cannulas. Product can change planes in an uncontrolled manner during needle injections, potentially leading to unintentional intra‐arterial placement. There is a paucity of data on the influence of injection angle on the dispersion patterns of soft tissue fillers. Materials and Methods: A total of 126 injection procedures were conducted in seven Caucasian body donors (four males, three females) with a mean age of 75.29 ± 4.95 years and a mean body mass index of 23.53 ± 3.96 kg/m 2 . Injection procedures were performed in various facial regions (forehead, scalp, zygomatic arch, mandibular angle), utilizing different needle sizes (25G, 27G, 30G) and different angles (90°, 45°, 10°). Layer‐by‐layer dissections were performed to verify the location of the injected product. Dissections were facilitated by the colored material. Results: Utilizing a 30G needle (compared to a 25G needle) reduces the superficial spread with OR 0.70 (95% CI, 0.48‐0.99) and P = 0.049, whereas injecting at 90° (vs 10° with the bevel down) increases the odds for superficial spread with OR 10.0 (95% CI, 7.11‐14.09) and P < 0.001. Conclusion: Precision during soft tissue filler injections, defined as the product remaining in the plane of intended implantation, can be enhanced by changing the needle size and the injection angle. Utilizing a 30G needle and injecting at a 10° angle with bevel facing down reduces the uncontrolled product distribution into superficial fascial layers.